Quality Analysis Of Library Information System Using Webqual Toward User Satisfaction - Dwi Januarita; Fauzan Romadlon (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
Websites for educational institutions is a form of information services that can be accessed online. One of the information services in educational institutions is library information system. This research focused on Institut Teknologi Telkom Purwokerto as an object of library information system implementation (dlibrary). Corresponding with the library strategy to become